2014
DOI: 10.1155/2014/392170
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Experimental Melioidosis following Immunisation with a Lipopolysaccharide-Protein Conjugate

Abstract: Melioidosis is a severe infectious disease caused by Burkholderia pseudomallei. It is refractory to antibiotic treatment and there is currently no licensed vaccine. In this report we detail the construction and protective efficacy of a polysaccharide-protein conjugate composed of B. pseudomallei lipopolysaccharide and the Hc fragment of tetanus toxin. Immunisation of mice with the lipopolysaccharide-conjugate led to significantly reduced bacterial burdens in the spleen 48 hours after challenge and afforded sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 43 publications
(49 reference statements)
1
23
0
Order By: Relevance
“…However, while the conjugate vaccine broadened the range of antibody isotypes, this candidate did not afford significantly greater protection than the unconjugated mix of free LPS and TetH c formulation (75% survival) [90]. containing Bp LPS, CPS, and protein antigens significantly protected mice against lethal aerosol challenge, with nearly 60% of mice surviving for 2 weeks post-infection [62].…”
Section: Glycoconjugate-based Subunit Vaccines Vaccine Formulations mentioning
confidence: 93%
See 2 more Smart Citations
“…However, while the conjugate vaccine broadened the range of antibody isotypes, this candidate did not afford significantly greater protection than the unconjugated mix of free LPS and TetH c formulation (75% survival) [90]. containing Bp LPS, CPS, and protein antigens significantly protected mice against lethal aerosol challenge, with nearly 60% of mice surviving for 2 weeks post-infection [62].…”
Section: Glycoconjugate-based Subunit Vaccines Vaccine Formulations mentioning
confidence: 93%
“…In the case of vaccines containing single proteins or unconjugated LPS, immunity is characterized by Th2-biased responses, which are not thought to be optimally effective against pathogens that can replicate intracellularly, such as Bp or Bm (For example, [89] [90]). Therefore, it is likely that polyvalent vaccines combining several antigens may be more effective in generating complete protective immunity against heterologous strains and diverse routes of infection [91] [4].…”
Section: Subunit Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibody responses directed against the various protein antigens were assessed by ELISA essentially as previously described [27] using 5 g/ml of each protein to coat ELISA wells. A reading of twice background or above was considered positive and the titre was determined to be the reciprocal of the final positive dilution.…”
Section: Igg1 and Igg2a Elisamentioning
confidence: 99%
“…In fact, previous studies have shown that proteins alone can provide significant, albeit incomplete, protection against Burkholderia challenge (11)(12)(13)(14). However, more recent studies have shown that when immunogenic proteins are incorporated in a glycoconjugate vaccine in conjunction with the highly antigenic Burkholderia lipopolysaccharide (LPS) or capsular polysaccharide (CPS), a more robust immune response is generated (15)(16)(17)(18). Our lab has previously demonstrated that the incorporation of a glycoconjugate with the surface of a gold nanoparticle can enhance the immune response and increase protection in a murine model of inhalational glanders, a disease caused by the closely related host-adapted pathogen B. mallei (17).…”
mentioning
confidence: 99%